THEORY AND METHODOLOGY OF TEACHING FOREIGN LANGUAGES: A MODERN PERSPECTIVE - To‘ychiyev Azamat Farxod o‘g‘li; Elmirzayeva Maftuna Dusmurod qizi (Innovation Science and Technology, 2025)
This article explores the theoretical foundations and methodological approaches in the field of foreign language teaching (FLT). It highlights the relevance of globalization in language education, discusses both traditional and innovative methods, and particularly emphasizes the effectiveness of the project-based learning approach. The study also addresses interdisciplinary integration, learner motivation, and the role of communicative competence in modern education.